Aerosol-Jet-Printed Encapsulation of Organic Photovoltaics - Basu, Robin; Siah, Kok Siong; Distler, Andreas; Häußler, Felix; Franke, Jörg; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Engineering Materials, 2023)
Organic electronic devices (OEDs) are prone to oxygen- and water-induced degradation and therefore need to be encapsulated with barrier materials. In this work, an aerosol jet (AJ)-printing process is developed to coat perhydropolysilazane (PHPS) directly onto OEDs by adapting the print setup and systematically optimizing the process parameters. Furthermore, a novel curing process that converts PHPS to silica barrier layers is developed by combining damp heat (DH) exposure with subsequent vacuum–UV irradiation. This two-step treatment is shown to be considerably faster and gentler than the state-of-the-art curing processes and also yields a quantitatively higher conversion. Both the printing and the conversion process are fully compatible with OED devices, which is demonstrated by a damage-free direct encapsulation of organic solar cells. The encapsulated cells show a significant reduction of degradation in DH conditions (65 °C/85% r.h.), maintaining >95% of their initial performance for >100 h. Complementary electroluminescence measurements reveal that the AJ-printed barrier layers effectively prevent lateral water ingress into the devices. Herein, the proof of principle is provided that AJ printing can be used to print barrier layers directly onto OEDs and is thus an industrially highly relevant technology to precisely encapsulate such devices even on 3D objects.
CRIS-Team Scopus Importer:2023-07-07
Keywords: aerosol jet printing; organic solar cells; perhydropolysilazane; printed barriers; solution-processed encapsulation

Fully solution-processed, light-weight, and ultraflexible organic solar cells - Güler, Ezgi; Distler, Andreas; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2022)
Organic photovoltaic (OPV) devices have the potential to be superior to other PV technologies for the use in applications that require very high flexibility or maximum specific power (power-per-weight ratio), such as textile integration, wearable electronics, or outer space applications. However, OPV devices also require encapsulation by barrier films to reduce the degradation driven by extrinsic factors, which in turn limits their flexibility and leads to lower specific power values. In this work, fully solution-processed (including both electrodes) semitransparent organic solar cells (OSCs) with performance comparable with conventional indium tin oxide-based devices are processed directly onto different barrier films of varying thicknesses. Direct cell fabrication onto barrier films leads to the elimination of the additional polyethylene terephthalate substrate and one of the two adhesive layers in the final stack of an encapsulated OPV device by replacing the industrial state-of-the-art sandwich encapsulation with a top-only encapsulation process, which yields significantly thinner and lighter 'product-relevant' PV devices. In addition to the increase of the specific power to 0.38 W g(-1), which is more than four times higher than sandwich-encapsulated devices, these novel OSCs exhibit better flexibility and survive 5000 bending cycles with 4.5 mm bending radius. Moreover, the devices show comparable stability as conventionally encapsulated devices under constant illumination (1 sun) in ambient air for 1000 h. Finally, degradation under damp heat conditions (65 degrees C, 85% rh) was investigated and found to be determined by a combination of different factors, namely (UV) light soaking, intrinsic barrier properties, and potential damaging of the barriers during (laser) processing.
CRIS-Team WoS Importer:2022-05-13
Keywords: solution-processability; specific power; organic photovoltaics; silver nanowire; transparent electrodes; flexible electronics; barrier films

Large-area organic photovoltaic modules with 14.5% certified world record efficiency - Basu, Robin; Gumpert, Fabian; Lohbreier, Jan; Morin, Pierre Olivier; Vohra, Varun; Liu, Yang; Zhou, Yinhua; Brabec, Christoph; Egelhaaf, Hans-Joachim; Distler, Andreas (Joule, 2024)
Organic photovoltaics (OPVs) have experienced a significant increase in power conversion efficiency (PCE) recently, now approaching 20% on small-cell level. Since the efficiencies on the module level are still substantially lower, focused upscaling research is necessary to reduce the gap between cells and modules. In this work, we present the upscaling of PM6:Y6-C12:PC61BM-based devices, processed in ambient air from non-halogenated solvents, from small-area cells to large-area modules with barely any performance loss. Supported by computational fluid dynamics simulations, an accelerated blade coating process that enables homogeneous coatings with <5% thickness deviation over 200 cm² is developed. Additional finite element method simulations are used to optimize the module layout and minimize the inevitable losses caused by electrode resistances and inactive interconnect areas to 1.9% and 3.5%, respectively. Finally, a 204-cm² OPV module with a certified PCE of 14.5% (15.0% on active area) is fabricated, which constitutes the new world record.
CRIS-Team Scopus Importer:2024-04-05
Keywords: certified world record efficiency; FEM simulations; laser patterning; OPVs; organic photovoltaics; process optimization; solar modules; solution-processed in ambient air

On the theoretical framework for meniscus-guided manufacturing of large-area OPV modules - Gumpert, Fabian; Janßen, Annika; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim; Lohbreier, Jan; Distler, Andreas (Progress in Organic Coatings, 2024)
For the manufacturing of thin films of solution-processable organic semiconductors, e.g. for organic photovoltaics (OPV), meniscus guided-coating techniques are the method of choice for large-scale industrial applications. However, the process requires an in-depth understanding of the respective fluid dynamics to control the resulting film thickness. In this article, we derive an analytical expression to describe the layer thickness of coatings manufactured with a trapezoidal-shaped applicator as a function of various fluid and process parameters. The analytical calculations are compared with results from computational fluid dynamics (CFD) simulations and experimental data for an industrially relevant OPV active material system. The good agreement of all three approaches demonstrates the potential of the analytical and simulative methods to minimize the number of time- and resource-consuming experiments. Furthermore, our theoretical model can be used to enhance the homogeneity of large-area coatings by means of an acceleration profile of the applicator that can compensate for the liquid loss during the coating process. The respective analytical expression is validated by simulated and experimentally obtained data for long-distance coatings. Finally, this approach is used to fabricate a large-area OPV module with new world record efficiency.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Accelerated coating velocity; Analytical description; Computational fluid dynamics; Meniscus-guided coating; Organic photovoltaics; Thin films

Over one-micron-thick void-free perovskite layers enable highly efficient and fully printed solar cells - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Distler, Andreas; Li, Chaohui; Forberich, Karen; Tian, Jingjing; Hemasiri, Naveen Harindu; Liu, Chao; Zhang, Jiyun; Yang, Fu; Le Corre, Vincent Marc; et al. (Energy and Environmental Science, 2025)
Commercialization of perovskite photovoltaics hinges on the successful transition from laboratory-scale fabrication to industrial-scale manufacturing. A key challenge in fully printed perovskite solar cells with non-reflecting back electrodes is the deposition of high-quality, over-one-micron-thick perovskite layers to minimize photocurrent losses from incomplete light absorption. However, the formation of voids at the substrate/perovskite interface impedes the fabrication of such layers. Here, phase-field simulations reveal that the bottom voids originate from trapped residual solvents, driven by nanocrystal aggregation at the liquid-vapor interface during drying. Guided by these insights, we introduce a two-dimensional (2D) perovskite layer-assisted growth strategy to promote heterogeneous nucleation at the substrate, accelerating 3D perovskite crystallization and preventing solvent entrapment. This strategy enables the formation of highly crystalline, monolithic perovskite films exceeding one micrometer in thickness. The resulting void-free films maximize photocurrent extraction, achieving power conversion efficiencies of 19.9% on rigid substrates and 17.5% on flexible substrates in fully printed perovskite solar cells with non-reflecting carbon electrodes.
CRIS-Team Scopus Importer:2025-05-30